O trabalho de assistentes sociais em uma unidade de cuidados paliativos - da Rosa, Tainara; Pereira da Silva, Ângela Maria (ILUMINURAS, 2021)
O trabalho de assistentes sociais em uma unidade de cuidados paliativos